2022
DOI: 10.3389/feart.2021.833302
|View full text |Cite
|
Sign up to set email alerts
|

Oil Occurrence States in Shale Mixed Inorganic Matter Nanopores

Abstract: In present paper, the mineral and fluid compositions of shale oil from the Songliao Basin are analyzed systematically using core samples, X-ray diffractometer (XRD), and gas chromatography (GC). The effects of shale mineral composition, pore size, temperature, and pressure on the mass density of the adsorbed layers are then studied utilizing molecular dynamics simulation. The results show that illite and quartz are predominant in the micro petrological components of the shale, and nC19 is the main carbon peak.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…We suppose that the first three peaks correspond to clearly discernible adsorption layer, while the last peak represents free shale oil, as evidenced by its density close to that of decane in its natural state, that is approximately 0.72 g cm −3 . 39,40 Upon gas injection, in the case of pure CO 2 , the peak of the oil layer density curve shifts to the free state region, indicating that the majority of adsorbed oil has converted to the free oil. 41 In the presence of CH 4 in the gas phase, the highest density peak of the oil layer remains in the adsorbed state region.…”
Section: Resultsmentioning
confidence: 99%
“…We suppose that the first three peaks correspond to clearly discernible adsorption layer, while the last peak represents free shale oil, as evidenced by its density close to that of decane in its natural state, that is approximately 0.72 g cm −3 . 39,40 Upon gas injection, in the case of pure CO 2 , the peak of the oil layer density curve shifts to the free state region, indicating that the majority of adsorbed oil has converted to the free oil. 41 In the presence of CH 4 in the gas phase, the highest density peak of the oil layer remains in the adsorbed state region.…”
Section: Resultsmentioning
confidence: 99%
“…Among the clay minerals, illite, MMT, and interstratified illite/MMT are the predominant constituents, with a small proportion of interstratified chlorite/MMT. According to the previous study of the research group [69], the whole rock analysis and clay mineral analysis were performed on rock samples of Member Qing 1 in the Songliao Basin using XRD. The results indicated that the primary components of inorganic matter were quartz and clay minerals.…”
Section: Modelingmentioning
confidence: 99%
“…Organic matter in shale can be divided into free state, adsorbed state, and dissolved state [50,51]. Generally speaking, free oil is mainly composed of light hydrocarbon components with good fluidity, mainly in the pore joints, microfractures, layer interstices, and matrix pores with a relatively large pore throat diameter [52].…”
Section: Shale Oil Occurrence Statusmentioning
confidence: 99%